Salicylic Acid, a Plant Defense Hormone, Is Specifically Secreted by a Molluscan Herbivore - Kästner, Julia (Public Library of Science, 2014)
Slugs and snails are important herbivores in many ecosystems. They differ from other herbivores by their characteristic mucus trail. As the mucus is secreted at the interface between the plants and the herbivores, its chemical composition may play an essential role in plant responses to slug and snail attack. Based on our current knowledge about host-manipulation strategies employed by pathogens and insects, we hypothesized that mollusks may excrete phytohormone-like substances into their mucus. We therefore screened locomotion mucus from thirteen molluscan herbivores for the presence of the plant defense hormones jasmonic acid (JA), salicylic acid (SA) and abscisic acid (ABA). We found that the locomotion mucus of one slug, Deroceras reticulatum, contained significant amounts of SA, a plant hormone that is known to induce resistance to pathogens and to suppress plant immunity against herbivores. None of the other slugs and snails contained SA or any other hormone in their locomotion mucus. When the mucus of D. reticulatum was applied to wounded leaves of A. thaliana, the promotor of the SA-responsive gene pathogenesis related 1 (PR1) was activated, demonstrating the potential of the mucus to regulate plant defenses. We discuss the potential ecological, agricultural and medical implications of this finding.